2022
DOI: 10.1002/adhm.202200290
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of High‐Performance Keratin‐Based Hemostatic Agents

Abstract: Keratins are considered ideal candidates as hemostatic agents, but the development lags far behind their potentials due to the poorly understood hemostatic mechanism and structure-function relations, owing to the composition complexity in protein extracts. Here, it is shown that by using a recombinant synthesis approach, individual types of keratins can be expressed and used for mechanism investigation and further high-performance keratin hemostatic agent design. In the comparative evaluation of full-length, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Hemostasis is the earliest application of keratin biomaterials, which was traced back to the 16th century. 13 We assumed that there was a difference in the hemostasis effect for the individual keratins. Therefore, we extracted four individual keratins (HK1, HK2, HK3, and HK4) using the H 2 O 2 /UV/TiO 2 method, and the individual keratin coating on PCL nanofibrous substrates was prepared using a physical deposition method (Figure 4a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemostasis is the earliest application of keratin biomaterials, which was traced back to the 16th century. 13 We assumed that there was a difference in the hemostasis effect for the individual keratins. Therefore, we extracted four individual keratins (HK1, HK2, HK3, and HK4) using the H 2 O 2 /UV/TiO 2 method, and the individual keratin coating on PCL nanofibrous substrates was prepared using a physical deposition method (Figure 4a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The keratins with different concentrations ranging from 1 mg/mL were coated on PCL nanofibrous substrates, which was prepared using a physical deposition method. 13 PCL nanofibers were put on a glass dish, and the keratin protein after the ultrafiltration process was dipped onto the surface of nanofiber. The keratin/PCL nanofibers were incubated at 37 °C for 2 h at 50 rpm until the dry nanofibers were obtained.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In addition, they cause polymerization of fibrinogen into fibrin which also contributes to hemostasis. In a comparative study by Wang et al [ 127 ], they observed that the α-helical segment contents of keratin are directionally proportional to its hemostatic activity, while the Tyr, Phe and Gln amino acids at the N-termini of the α-helices in keratins play an important role in fibrin polymerization. He et al [ 128 ] fabricated keratin-based hydrogels extracted from human hair, named K-gels ( Fig.…”
Section: Polypeptide Materials For Hemostasismentioning
confidence: 99%
“…Moreover, some have pointed out that, as biogenic polypeptides, it is difficult to control the keratin's amino acid composition, batch-to-batch difference, and complex keratin-related proteins. These have stalled the exploration of its use for hemostasis [ 103 ]. Synthesis of recombinant keratin through bioengineering methods may ultimately solve the above problems.…”
Section: Molecular Structure Design Of the Hemostasis Materialsmentioning
confidence: 99%